Psychosocial rehabilitation and mental health (24th European Congress of Psychiatry materials review) - Frankova, Iryna; Krasnova, Polina (Psychosomatic Medicine and General Practice, 2016)
Background: Mental illness - is a heavy burden of modern society and may be underestimated. There are several reasons: the high prevalence of this category of disorders, high level of stigmatization, treatment gap between those who are mentally ill and those will be treated. The economic crisis and the lack of resources, make psychosocial rehabilitation of mental disorders even more complicated. Methods: This review is based on materials of the 24th Congress of the European Psychiatric Association (April 2016, Madrid), the participants of the "Eastern European Academy of the World Psychiatric Association and "Servier" company specifically for psychiatric journals of WPA Zone 10 (East European Educational WPA-Servier Academy - «EEE WPA-Servier Academy». The review will present materials from several symposiums: "Psychosocial rehabilitation and mental health", "Overcoming the stigma of mental disorders: recent advances and initiatives," "Fight stigma: a global challenge", and state-of-the-art report, "Psychosocial interventions in schizophrenia ». Results: As result, we anticipate that this review will distribute and promote knowledge about high quality standards and evidence-based research and treatment methods among the modern community of mental health experts. Conclusion: Current approach in psychosocial rehabilitation of severe mental disorders has changed significantly due to the data of evidence-based medicine, the use of effective, superior methods suggests a good outcome for a larger number of patients.